PHYLOGENETIC ANALYSIS OF CYTOCHROME OXIDASE SUBUNIT I (COI) GENE SEQUENCES OF MITOCHONDRIAL DNA OF PARNASSIUS SPP. (LEPIDOPTERA; PAPILIONIDAE; PARNASSIINAE) - SOUMENDRANATH CHATTERJEE; TUHIN SUBHRA GHOSH; RAHUL MISRA; JAGANNATH CHATTOPADHYAY (The Bioscan, 2010)
Cytochrome oxidase subunit I (COI) gene sequences of mitochondrial DNA of different species of the genus Parnassius downloaded from NCBI (www.ncbi.nlm.nih.gov) were aligned and analyzed to determine the diversity in respect to the percentage of Adenine, Thymine, Guanine and Cytosine, AT content, G+C content, basic melting temperature, relative melting temperature. Mean values of AT content, GC content and Relative melting temperature were 71.7713, 28.2564 and 0.363666 respectively showing a linear regression between GC content and the mean value of Relative melting temperature.